Tax Procedure Education for MSME Business Operators in Kebon Manggis, Jakarta (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) make a significant contribution to the national economy; however, the level of tax literacy and compliance among MSME actors remains relatively low. This community service program aimed to enhance the understanding and practical skills of MSME actors in Kebon Manggis, East Jakarta, regarding business taxation procedures. The implementation method comprised three stages: preparation, training, and evaluation. The training was delivered through lectures and practical demonstrations covering tax obligations, the MSME Final Income Tax (PPh Final) rate, procedures for Taxpayer Identification Number (NPWP) registration, and the use of digital tax systems such as e-Billing and e-Filing. Program effectiveness was assessed using a pre-test–post-test design involving 18 participants, with data analyzed using the Wilcoxon Signed-Rank test. The results indicated a significant difference in participants’ tax literacy knowledge before and after the training. These findings suggest that tax education is effective in improving tax literacy among MSME actors. The program has implications for strengthening business legality, professionalism, and sustainability; nevertheless, follow-up mentoring is needed to ensure the consistent implementation of tax obligations competitive school culture.